2009
DOI: 10.1134/s0036024409040281
|View full text |Cite
|
Sign up to set email alerts
|

Charge recombination in excited donor-acceptor complexes with two absorption bands

Abstract: -The dynamics of charge recombination in a photoexcited donor-acceptor complex comprising 1,2,4-trimethoxybenzene (electron donor) and tetracyanoethylene (electron acceptor) in several polar solvents (acetonitrile, valeronitrile, and octanonitrile) was studied in terms of the stochastic approach. The Gibbs energy of charge recombination and the reorganization energies of the medium and quantum and vibrational degrees of freedom were found by fitting the stationary absorption spectrum. The electronic couplings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The two-staged regime most clearly manifests if the solvent reorganization energy noticeably exceeds the CR free-energy gap (black solid line in frame C in Figure ). Otherwise, the CR kinetics closely approaches the single-nonequilibrium-stage regime for strong and intermediary exergonic CR and with an increase in electronic coupling …”
Section: Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The two-staged regime most clearly manifests if the solvent reorganization energy noticeably exceeds the CR free-energy gap (black solid line in frame C in Figure ). Otherwise, the CR kinetics closely approaches the single-nonequilibrium-stage regime for strong and intermediary exergonic CR and with an increase in electronic coupling …”
Section: Results and Discussionmentioning
confidence: 88%
“…Otherwise, the CR kinetics closely approaches the single-nonequilibrium-stage regime for strong and intermediary exergonic CR and with an increase in electronic coupling. 57…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second, much slower, stage was detected only in a fast solvent (ACN), and it disappeared in slower solvents, valeronitrile and octanonitrile. Modeling the kinetics of charge recombination confirmed that its efficiency at the nonequilibrium stage increases with increasing the solvent relaxation time, which greatly reduces the yield of the thermalized excited state, and its decay becomes invisible in the experimental transition spectra in slow solvents …”
Section: Resultsmentioning
confidence: 97%
“…The kinetics of ET between individual vibrational sublevels can be described in the framework of the stochastic approach generalized to account for the decay of both the reactant and the product states. A set of two coupled differential equations ,,,,, for the probability distribution functions along the reaction coordinate, Q , for the reactant state, ρ r ( Q , t ), and the product state, ρ p ( Q , t ) is solved analytically by Green’s function method. Here, ℏ is the Planck constant, and δ­( Q ) is the Dirac delta function.…”
Section: Theory and Computational Detailsmentioning
confidence: 99%